Perihilar Cholangiocarcinoma – Novel Benchmark Values for Surgical and Oncological Outcomes From 24 Expert Centers. Issue 5 (November 2021) - Mueller, Matteo; Breuer, Eva; Mizuno, Takashi; Bartsch, Fabian; Ratti, Francesca; Benzing, Christian; Ammar-Khodja, Noémie; Sugiura, Teiichi; Takayashiki, Tsukasa; Hessheimer, Amelia; Kim, Hyung Sun; Ruzzenente, Andrea; et al.
Abstract : Objective: The aim of this study was to define robust benchmark values for the surgical treatment of perihilar cholangiocarcinomas (PHC) to enable unbiased comparisons. Background: Despite ongoing efforts, postoperative mortality and morbidity remains high after complex liver surgery for PHC. Benchmark data of best achievable results in surgical PHC treatment are however still lacking. Methods: This study analyzed consecutive patients undergoing major liver surgery for PHC in 24 high-volume centers in 3 continents over the recent 5-year period (2014–2018) with a minimum follow-up of 1 year in each patient. Benchmark patients were those operated at high-volume centers (≥50 cases during the study period) without the need for vascular reconstruction due to tumor invasion, or the presence of significant co-morbidities such as severe obesity (body mass index ≥35), diabetes, or cardiovascular diseases. Benchmark cutoff values were derived from the 75 th or 25 th percentile of the median values of all benchmark centers. Results: Seven hundred eight (39%) of a total of 1829 consecutive patients qualified as benchmark cases. Benchmark cut-offs included: R0 resection ≥57%, postoperative liver failure (International Study Group of Liver Surgery): ⩽35%; in-hospital and 3-month mortality rates ⩽8% and ⩽13%, respectively; 3-month grade 3 complications and the CCI: ⩽70% and ⩽30.5, respectively; bile leak-rate: ⩽47% and 5-year overall survival of ≥39.7%. Centers operating mostly on complex cases disclosed better outcome including lower post-operative liver failure rates (4% vs 13%; P = 0.002). Centers from Asia disclosed better outcomes. Conclusion: Surgery for PHC remains associated with high morbidity and mortality with now the availability of benchmark values covering 21 outcome parameters, which may serve as key references for comparison in any future analyses of individuals, group of patients or centers. Abstract : Supplemental Digital Content is available in the text